Emotional Intelligence Skills and Self-efficacy Levels: Physical Education Teachers' Perspective - AL-Adwan, Fatima Eid Zaid; Al – Khayat, Majed Mohammad (European Scientific Journal, ESJ, 2016)
The aim of this study is to investigate the relationship between emotional intelligence skills and self-efficacy levels among physical education teachers from the teachers' own perspective. The researchers developed two scales that measure the emotional intelligence skills; and another one to measure self-efficacy levels for physical education teachers. These two scales were applied on (70) teachers from public and private schools of the Salt Directorate of Education in Jordan. The results show a strong relationship between the emotional intelligence skills and self-efficacy levels among physical education teachers. Therefore, the results also showed that the physical education teachers have high levels of emotional intelligence skills and self-efficacy levels. Also, the results show the presence of statistically significant differences between teachers in the emotional intelligence skills for the benefit of male teachers, and between public and private schools for public schools. The researchers have recommended that it is necessary to teach some training programs about emotional intelligence to physical education teachers in both public and private schools and universities.